Social Transformation in Modern Society: A Literature Review on the Role of Technology in Social Interaction - Hanandini, Dwiyanti (Jurnal Ilmiah Ekotrans & Erudisi, 2024)
This article examines the transformative influence of technology on social interaction in contemporary culture. The structure of contemporary society has been considerably altered by technological advancements, particularly in the digital domain. This study used a literature review methodology to investigate the impact of technology on social dynamics, encompassing aspects such as connectivity, communication, and the establishment of social networks. This article concludes that technology has significantly influenced the rise of social connection but has also presented issues such as the depersonalization of interactions and heightened dependence on data. These findings emphasize the necessity for a more extensive comprehension of digital transition and its influence on social life.